Urgensi Ijtihad Saintifik dalam Menjawab Problematika Hukum Transaksi Kontemporer - Fauzi M (NALAR FIQH: Jurnal Hukum Islam, 2011)
This article will discuss abaout the rational urgency to do scientific ijtihad to answer the legal issues of contemporary transaction and also perform scientific ijtihad basis and examples of scientific ijtihad in answering legal issues of contemporary transactions.